The importance of student assistance in times of pandemic: An account of experiences of the Nucleus for Educational Development of the Federal University of Pampa - Uruguaiana Campus (Research, Society and Development, 2022)
The article focuses on the Student Assistance policies carried out by the Educational Development Nucleus - NuDE of the Federal University of Pampa, Unipampa, Campus Uruguaiana, expressed in financial support actions for Student Assistance scholarship recipients, with the aim of problematizing the relationship between socioeconomic vulnerability with the challenges brought by the pandemic, specifically the period of social isolation and Emergency Remote Learning (ERE). The discussion presented here strives to highlight the strong connection between students in a situation of social vulnerability and their permanence, an understanding that supported the survey of these subjects' levels of satisfaction. The study is based on the theoretical assumptions of participatory school management, inserting policies in a democratic perspective. Methodologically, the research, of a quantitative-qualitative, exploratory nature, sought to understand the role of policies from the perspective of those assisted, adopting, as a theoretical framework for analysis, the anthropology of development. Due to the extent of the investigation, this article focuses the first phase referring to the general satisfaction and challenges faced by the studied population, based on three main categories: mental health, financial balance and challenges to adapt to the ERE translated into five questions posed in the data collection instrument. The inclusion condition was the family income not exceed a minimum wage and a half per person. The results showed that Student Assistance actions (financial aid to supplement food, rent and connection infrastructure) have contributed to assisted students. The aid was also expanded to cover emergency demands (Aid to Digital Inclusion) to improve access to the ERE, promoting the permanence of students, even in the midst of the COVID-19 crisis.